Analisis Hygiene Dan Sanitasi Makanan Di Instalasi Gizi Rumah Sakit - Rahma Adiyaksa Gea Doktriana; Mohamad Yaser; Jefri Wahyudi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Food sanitation hygiene is an effort to control factors in places, equipment, people and food ingredients that can or may cause health problems, disease or food poisoning. The aim of this research is to determine the Hygiene and Sanitation of Hospital Food according to PERMENKES No.1096/Menkes/Per/VI/2011 Concerning Jasaboga Sanitation Hygiene in Hospitals. This research uses a qualitative approach that describes the problem and focuses on the research. This research carried out in-depth interviews with 5 informants. This research was conducted in the hygiene and sanitation unit at Hospital. Collecting data by conducting observations, interviews, document analysis and documentation. Based on research results related to SOP Hygiene and Food Sanitation are appropriate, Selection of Food Ingredients is appropriate, Storage of Food Ingredients is appropriate, Food processing is still not appropriate where the cooking utensil storage rack is not closed to protect it from vectors, Storage of Finished Food Ingredients is appropriate, Serving The food is still not in accordance with the Regulation of the Minister of Health of the Republic of Indonesia No.1096 of 2011 because it uses wooden tables which are only covered with plastic. Suggestions for the Hospital for the environmental health unit are to provide cooking utensil storage racks with covers so that they can be protected from vectors and for the Environmental Health unit, it is hoped that the serving table should be replaced with a table made from stainless steel.